B Cell Responses to CpG Correlate with CXCL16 Expression Levels in Common Variable Immunodeficiency. (1st February 2012) - Lougaris, Vassilios; Baronio, Manuela; Vitali, Massimiliano; Tampella, Giacomo; Soresina, Annarosa; Badolato, Raffaele; Plebani, Alessandro
Abstract : Broad Toll-like receptor 9 (TLR9) signalling defects after CpG in vitro stimulation have been described in common variable immunodeficiency (CVID). CXCL16, a surface receptor, was recently shown to influence cell responses to CpG. We evaluated the expression and function of CXCL16 on B cells from healthy controls and CVID patients. We report that CXCL16 is normally expressed on B cells throughout peripheral maturation. Decreased B cell expression of CXCL16 was observed in a subgroup of CVID patients that correlated with defective in vitro responses to CpG (such as upregulation of CD69, CD86, AICDA, IL-6, and TLR9). Our data suggest that expression levels of a surface receptor, namely, CXCL16, correlate with B cell responses mediated by TLR9 in common variable immunodeficiency.